Introducing the concept of sono-chemical potential: A phenomenological model for ultrasound assisted extraction - Orphanides, Antia; Goulas, Vlasios; Gekas, Vassilis (My University, 2014)
The current study presents a mathematical formulation that describes the role of ultrasonic irradiation in ultrasonic assisted extraction with thermodynamic terms. This model described the influence of ultrasound irradiation on the chemical potential of extracted compounds and predicted the increase of the yield of extraction using ultrasound irradiation. The term sono-chemical potential was described for the first time in an analogy to the piezo- or the electrochemical potential. Subsequently, the derived formula was applied on the extraction of polyphenols from spearmint, where the model showed the increase factor in the extracted amounts during ultrasound assisted extraction; the predicted value for a five minute extraction was 2.89 and the experimental values were 2.99, 2.92 and 2.32 for the hydroxycinnamic acid derivatives content, the antioxidant activity and the total phenolics respectively. The model could be further verified and used to explain the enhanced recovery of various compounds from diverse matrixes.
Keywords: Chemical potential; Extraction kinetics; Mass transfer; Mathematical modeling; Polyphenols; Ultrasonic irradiation